The gender neutral bible controversy is the age of political correctness altering the meaning of God's words? - Poythress, Vern Sheridan; Grudem, Wayne A. 1948- (Fearn, Scotland Christian Focus, 2003)
Includes bibliographical references and index.
Keywords: Bible -- hermeneutics; Gender -- biblical teaching